Profesionalitas Kepala Madrasah dalam Melaksanakan Manajemen Siswa - Lukman Hakim (Journal of Educational Research, 2022)
This article examines the professionalism of the Principal in implementing student management at MTs Negeri 2 Muaro Jambi for the 2021/2022 academic year. The main problem is why does the principal in carrying out student management at MTs Negeri 2 Muaro Jambi seem less professional? This research is a qualitative research that will reveal, find and explore information about the professionalism of school principals in implementing student management. This study found that the principal in implementing student management at MTs Negeri 2 Muaro Jambi was less professional because it had not been supported by adequate funds and facilities according to student development needs. However, solid collaboration between the management team, available training to increase the experience of principals and teachers, as well as two-way communication are factors that support the professionalism of the principal in implementing student management. The principal continues to strive to optimize his professionalism in carrying out student management at MTs Negeri 2 Muaro Jambi by means of; (a) increasing leadership commitment, (b) continuous improvement according to the vision, and (c) the availability of an adequate quality budget. Artikel ini mengkaji tentang profesionalitas Kepala Sekolah dalam melaksanakan manajemen siswa di MTs Negeri 2 Muaro Jambi Tahun pelajaran 2021/2022. Permasalahan utamanya adalah mengapa Kepala Sekolah dalam melaksanakan manajemen siswa di MTs Negeri 2 Muaro Jambi terkesan kurang profesional? Penelitian ini merupakan penelitian kualitatif yang akan mengungkapkan, menemukan dan menggali informasi tentang profesionalitas kepala sekolah dalam melaksanakan manajemen siswa. Penelitian ini menemukan bahwa Kepala Sekolah dalam melaksanakan manajemen siswa di MTs Negeri 2 Muaro Jambi kurang profesional karena belum didukung oleh dana dan sarana yang memadai sesuai kebutuhan pengembangan siswa. Akan tetapi adanya kerjasama yang solid antara tim manajemen, pelatihan yang tersedia untuk menambah pengalaman kepala sekolah dan guru, serta komunikasi yang mengalir dua arah merupakan faktor pendukung profesionalitas Kepala Sekolah dalam melaksanakan manajemen siswa. Kepala Sekolah tetap berupaya mengoptimalkan profesionalitasnya dalam melaksanakan manajemen siswa di MTs Negeri 2 Muaro Jambi dengan cara; (a) meningkatkan komitmen pimpinan, (b) perbaikan terus menerus sesuai visi, dan (c) ketersediaan anggaran mutu secara memadai.